Reliability and validity of the Advanced Basal Cell Carcinoma Index (aBCCdex). (11th June 2015) - Mathias, S.D.; Chren, M.M.; Crosby, R.D.; Colwell, H.H.; Yim, Y.M.; Reyes, C.; Chen, D.M.; Fosko, S.W.
Summary: Background: Patient‐reported outcome (PRO) questionnaires were recently developed specifically for use with patients with advanced basal cell carcinoma (aBCC) and basal cell carcinoma naevus syndrome (BCCNS). Objectives: To evaluate the measurement properties of PRO questionnaires for use in patients with aBCC or BCCNS. Methods: In total 129 patients from 10 clinical sites in the U.S.A. and the BCCNS Support Network completed the two newly developed questionnaires multiple times over 3 months. Patients also completed the Skindex‐16 and the 12‐Item Short‐Form Health Survey as collateral measures. Psychometric properties of the questionnaires were evaluated, including internal consistency and test–retest reliability, construct and known‐groups validity, and responsiveness. Results: Based on the results of exploratory factor analysis and clinical input, the two newly developed questionnaires were combined into a single questionnaire, called the aBCCdex, which is relevant for patients with both aBCC and BCCNS. The internal consistency reliability was acceptable, and all aBCCdex scale scores correlated significantly with conceptually similar scales. When divided into groups that differed based on scores from collateral measures, aBCCdex scale scores differentiated between groups (known‐groups validity) and were responsive to change. Conclusions: The aBCCdex is a brief and comprehensive questionnaire appropriate for use with patients with aBCC and BCCNS. Its reliability and validity have been confirmed. Further research is necessary to estimate the minimally important difference in a larger patient population. Abstract : What's already known about this topic? The effect of advanced basal cell carcinoma (aBCC) and basal cell carcinoma naevus syndrome (BCCNS) on patients can be substantial, impacting emotional, social and physical functioning. Available patient‐reported outcome (PRO) literature in aBCC and BCCNS is limited and no validated PRO measure exists. What does this study add? The aBCCdex, a reliable and valid instrument for aBCC and BCCNS, is useful in clinical practice and clinical trials.